Consumer motivation as a basis for forming an effective communication mix - Skryhun, Natalya; Krainiuchenko (Fornolyak), Olga; Bezpalko, Olena (My University, 2012)
Essence of complex of promotion and his elements is considered, grounded necessity account of type and level motivation of consumer at forming of communication mix, the types of consumers are selected taking into account the level of their motivation, which allows developing effective strategy advancement of the product.
Keywords: promotion; communication mix; consumer; motivation; advertising; need; просування; комунікаційний мікс; споживач; мотивація; реклама; потреба; коммуникационный микс; потребитель; мотивация; кафедра економіки праці та менеджменту; потребность; кафедра маркетингу; продвижение